The implications of population ageing on savings rates - Nkomo, Nomusa Yolanda; Adanlawo, Eyitayo Francis (Management and Entrepreneurship: Trends of Development, 2023)
Changes in population structure can have a great impact on savings rates. This study investigated the relationship that exists between the aging population and the savings rate in South Africa. The gross savings of South Africa from 1995 to 2017 was analysed. A fixed effect model and a random effect model were used as baselines for arbitrary correlations between unobserved heterogeneity and independent variables. The Hausman test was utilized to find a more efficient and consistent model that produces consistent results. The argument of the Lice Cycle Hypothesis developed by Modigliani (1970) and those previous research findings in which the rising older population has a tendency to decrease the rates of savings were followed in this paper. The findings revealed that an increase in old-age dependency does not cause the level of savings to decline but will rather lead to an increase in savings. The findings agree with the bequest theory, which states that old people save up their money for their upcoming generation. Due to the findings obtained in this paper, economic policies that aim to increase savings through demographics might not be relevant and are therefore not suggested. JEL Classification: J11, J14, E21